Methodological issues associated with clinical trials in epilepsy. Issue 10 (3rd October 2017) - Ferlazzo, Edoardo; Sueri, Chiara; Gasparini, Sara; Russo, Emilio; Cianci, Vittoria; Ascoli, Michele; De Sarro, Giovambattista; Aguglia, Umberto
ABSTRACT: Introduction : despite methodological advances in epilepsy clinical trials, the proportion of patients reaching seizure-freedom has not substantially changed over the years. We review the main methodological limitations of current trials, the possible strategies to overcome these limits, and the issues that need to be addressed in next future. Area covered : references were identified by PubMed search until March 2017 and unpublished literature was searched on ClinicalTrials.gov. Add-on trials mainly involve refractory epilepsy subjects, reducing overall response to the investigational drug. The inclusion of subjects with earlier disease from less developed countries has partially allowed overcoming this limitation, but has introduced more random variability of results. Monotherapy trials rise methodological, economical, and ethical concerns with different regulatory requirements in European Union and in the United States of America. Newer trial designs, such as futility trials or 'time-to-event' design, have been implemented. Moreover, both add-on and monotherapy trials results might be affected by patient's ability to recognize and record seizures, and by randomness of seizures occurrence over time. Possible strategies to achieve more reliable outcomes are detailed. Expert commentary : clinical trial methodology needs to be optimized to better address regulatory agencies requirements and to encounter both patients' and clinicians' needs.